Напрями вдосконалення діючих механізмів управління інноваціями в умовах модернізації економіки України - Землянкін, А.І.; Підоричева, І.Ю. (Економіка промисловості, 2015)
На основі проведених досліджень стану та результативності діючих механізмів управління інноваціями розроблено пропозиції щодо їх удосконалення та підвищення стимулюючої дії на інноваційні процеси, що протікають в українській економіці. На основе проведенных исследований состояния и результативности действующих механизмов управления инновациями разработаны предложения по их совершенствованию и повышению стимулирующего воздействия на инновационные процессы, протекающие в украинской экономике. The article is devoted to proposals on improvement of the existing mechanisms of innovation management in the conditions of modernization of the national economy. Today, innovations are firmly recognized as one of the main sources of sustainable economic growth for advanced and emerging economies. That is why the stimulation of innovative potential of the countries shocked by the crisis is considered as a possible catalyst for revitalizing their economies. More active government intervention to support innovation comes to the fore. For many years in Ukraine there has been a business model that has been based solely on the use of raw materials and cheap labor to produce more income. As a result, Ukraine continues to stay on the resource development stage of the economy. It is clear that further advance along this way directly threatens the national safety of Ukraine. In such circumstances, it is necessary to change approaches to the management of innovation processes, increase efficiency and productivity of the mechanisms of innovation management. In the article the mechanisms of innovation management are considered in the context of modernization of national economy as a set of the control system components influencing innovation processes and reflecting certain aspects of management - goals, principles, functions, tasks, controls, personnel, methods, resources, and tools.Such mechanisms of innovation management are allocated as the main: mechanisms for planning and forecasting, coordinating and monitoring the innovation; financial and economic mechanism and legal mechanism of innovation management. Proposals are grouped singly for each of the selected control mechanisms. In particular, within the mechanism of planning and forecasting the innovative activity at the government level it is proposed to establish a special commission for the development of National Innovation Strategy of Ukraine as a single comprehensive document accumulating political initiatives, offers of scientific community, businesses and all other interested parties. It is worth noticing that all of these mechanisms should be used comprehensively, using the methods and tools of public policy in a certain sequence and interrelation with the involvement in management decisions of all stakeholders and participants in innovation processes.